-4
Объяснение:
-2(x+3)=2x-1
-2x-6=2x-1
-2x-6-2x+1=0
-4x-5=0 / *(-1)
4x+5=0
a=0;b=4;c=5
D=b^2-4ac
D=16-4*0*5
D=16
x1,2=-b+/-корень D / 2a
x1,2=-4+/-4 / 2
x1=-8/2; x1=-4
x2=0/2; x2=0
x={7/60; 11/60}, x₁+x₂=7/60+11/60=18/60=0,3
Объяснение:
sin5πx-cos5πx=√6/2
(√2/2)(sin5πx-cos5πx)=(√6/2)(√2/2)
sin(π/4)sin5πx-cos(π/4)cos5πx=√3/2
-cos(π/4+5πx)=√3/2
cos(π/4+5πx)=-√3/2
π/4+5πx=±arccos(-√3/2)+2kπ=±(π-arccos(√3/2))+2kπ=±(5π/6)+2kπ, k∈Z
1/4+5x=±5/6+2k
5x=±5/6-1/4+2k
x=±1/6-1/20+0,4k
1) x=1/6-1/20+0,4k=(7+24k)/60
0<(7+24k)/60<0,5
0<7+24k<30
-7/24<k<23/24, k∈Z⇒k=0⇒(7+0)/60=7/60
2) x=-1/6-1/20+0,4k=(-13+24k)/60
0<(-13+24k)/60<0,5
0<-13+24k<30
13/24<k<43/24, k∈Z⇒k=1⇒x=(-13+24)/60=11/60
x₁+x₂=7/60+11/60=18/60=0,3
-2х(х+3)=2х-1
-2х-6=2х-1
-2х-2х=-1+6
-4х=5
Х=-5/4